Amelioration Du Systeme De Management De Qualite Via Une Contribution A La Mise En Place D’un Systeme De Management De Securite Dans Une Societe Multinationale Au Maroc - Aziz Bahlouli; Chaouch Abdelaziz; Ghizlane Hajjaj; Mahjoub Aouane (European Scientific Journal, ESJ, 2018)
Managing staff security has become a global requirement and challenge. Moroccan companies are obliged to guarantee the safety of their personnel through a security management system. The implementation of the SMS (Safety Management System) has now become a regulatory requirement. This article presents a study carried out in a multinational company, a production and packaging unit for fresh fruits and vegetables, with a view to setting up an SMS, in an approach aimed at improving the quality system of the company.